Plus ça change . . . Instruction for Information Literacy in Canadian University and College Libraries - Julien, Heidi; Tan, Maria (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper reports results of a longitudinal survey of information literacy instruction practices in Canadian academic libraries. Comparisons are made with Canadian data collected over the past 15 years, as well as with international data. The research has practical value to establish benchmarks and to identify opportunities for service improvement. Cette communication présente les résultats d’un sondage longitudinal sur les pratiques d’enseignement de la maîtrise informationnelle dans les bibliothèques académiques au Canada. On y compare les données recueillies au Canada au cours des quinze dernières années ainsi que des données internationales. La recherche comporte une valeur pratique pour établir un repère et déterminer les occasions d’amélioration des services.